ANALISIS RASIO LIKUIDITAS, RASIO SOLVABILITAS DAN RASIO PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN PT TELEKOMUNIKASI INDONESIA Tbk PERIODE 2015-2021 - Lupi, Muhamad; Hidayat, Arif (Journal of Research and Publication Innovation, 2023)
The purpose of this study is to analyze liquidity ratios, solvency ratios and profitability ratios to measure the level of financial performance at PT Telekomunikasi Indonesia Tbk. This research uses quantitative methods. The data used by this researcher is in the form of financial statements of PT Telekomunikasi Indonesia Tbk for the period 2015 to 2021. The standard used in this analysis is an industry standard guideline according to Kasmir (2018: 134-158) related to liquidity ratios, solvency ratios and profitability ratios. It can be seen from the results of this study that the liquidity ratio in the form of cash ratio at PT Telekomunikasi Indonesia Tbk for the period 2015 to 2021 is in a good position but the current ratio is in a bad position. Meanwhile, the solvency ratio in the form of debt to equity ratio and debt to asset ratio at PT Telekomunikasi Indonesia Tbk for the period 2015 to 2021 is in a poor position, for the profitability ratio in the form of return on asset and return on equity at PT Telekomunikasi Indonesia Tbk for the 2015 to 2021 period is not good